Developing and Validating a Game-Based Financial Literacy Assessment for Early Childhood: An Evidence-Centered Design Approach - Nurlaeli Fitriah; Aris Budianto; Saiful Hikmah (International Journal of Learning Reformation in Elementary Education, 2026)
Financial literacy is an important skill that children need to have to face future economic challenges. However, the level of financial literacy among young children is still low, with many children lacking an understanding of basic financial concepts such as money management, saving, and distinguishing between needs and wants. Although various financial literacy education programs have been introduced, measuring the financial literacy of early childhood remains a challenge, as traditional evaluation methods are often ineffective and unsuitable for children's developmental characteristics. This article aims to develop and validate a game-based assessment instrument for measuring the financial literacy of early childhood, designed using the Evidence-Centered Design (ECD) framework. This study tested the effectiveness of game-based assessment in measuring financial literacy in early childhood through trials in two kindergartens in Malang, East Java, involving 100 students aged 5-6 years. The results of this study indicate that this game-based financial literacy instrument is enough valid and reliable for measuring children's financial literacy and the measurement results can be used as an evaluation tool for educators or institutions in developing more effective financial education policies that are appropriate to children's needs in schools.